NAFKAH SUAMI TERHADAP ISTRI YANG PINDAH AGAMA DITINJAU MENURUT KOMPILASI HUKUM ISLAM (STUDI KASUS PUTUSAN NOMOR 361 K/AG/2016) - Zivra Dwi Tarrevia; Imelda Martinelli (Jurnal Hukum Adigama, 2020)
One of the problems on supporting the livelihood of a apostate wife can be find in supreme court decision number 361 k/ag/2016 concerning a civil case between Dwi Andayani, wife of Suroto bin Abu Bakri. On its decision, Dwi Andayani has been divorced by the decision of the court for change of religion which makes Dwi Andayani unsatisfied with the decision. Ever since splitting up, Dwi Andayani's livelihood has not been paid for. This leads to a request for cassation by Dwi Andayani. The emerging question is how does a husband paid for the livelihood of an apostate wife? to answer the question the writer uses normative research method, with normative juridicial approach. The supreme court decision orders to only pay for mut'ah only. Wives shall also receive madhliyah payments which is credited by the husbands towards the wives during marriage. Thus, the government shall be clear on divorce by change of religion and which payments should be received by the wives. Religion based institution shall also give understanding about marriage to maintain the integrity of each marriages.